MINIMIZING PROJECT COMPLETION DELAYS AND OPERATIONAL COST (A CASE STUDY: PT. BINA KARYA (PERSERO) PROJECT) - Noviansyah, Angga
The construction industry has become a contributor to Indonesia's economic growth (BPS, 2021), although, during the current pandemic, the development of the construction industry is relatively stable and is expected to grow on a global scale in the coming years (McKinsey, 2020). To increased economic growth through construction projects, the Indonesian government is accelerating to accelerate the implementation of construction projects while still paying attention to controlling costs, time, quality, and accompanying project administration, so that government regulations and the role of construction management consultants are needed to fulfill them.